2015
DOI: 10.1021/acsphotonics.5b00422
|View full text |Cite
|
Sign up to set email alerts
|

Necklace State Hallmark in Disordered 2D Photonic Systems

Abstract: Necklace states arise from the coupling of otherwise confined modes in disordered photonic systems and open high transmission channels in strongly scattering media. Despite their potential relevance in the transport properties of photonic systems, necklace state statistical occurrence in dimensions higher than one is hard to measure, because of the lack of a decisive signature. In this work we provide an efficient method to tell apart in a single measurement a coupled mode from a single localized state in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Fig.1 panel (a) and (b) show the distribution of the resonant complex poles Λ n , color-coded according to the log 10 values of the Mode Spatial Extent (MSE), when the optical density is set equal to 1 and to 15, respectively. The MSE parameter characterizes the spatial extent of a photonic mode [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig.1 panel (a) and (b) show the distribution of the resonant complex poles Λ n , color-coded according to the log 10 values of the Mode Spatial Extent (MSE), when the optical density is set equal to 1 and to 15, respectively. The MSE parameter characterizes the spatial extent of a photonic mode [20].…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery by P. W. Anderson in 1958 that strong disorder can inhibit electronic transport [1], the quest an optical counterpart of strong localization has motivated an intense research activity in photonic random media [2,3]. Random lasers [4,5], multiple scattering in random media [3,[6][7][8][9][10][11][12][13][14][15][16][17], local density of states modification induced by multiple scattering [18,19], tuning and controlling of coupled-random modes [20][21][22], and speckle pattern information decoding [23][24][25], are some of the important results recently achieved in the field of disordered photonics. However, there is no unquestionable observation of light localization in three-dimensional (3D) uniform random systems (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Our method can be easily extended to a larger number of nanocavities by adding more pump spots to the system. Resonance tuning with crosstalk compensation is likely to become a valuable method for any type of systems where disorder influences resonance states is required such as optomechanical systems 9,28 , many resonator systems [29][30][31][32] , disordered necklace states 12,33 and complex boson sampling networks 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…However, unavoidable fabrication disorder in nanophotonic structures causes scattering which leads to frequency detuning, signal attenuation, and eventually localizes optical modes which ruins the transmission properties of the whole system 11,12 . Even state-of-the-art nanofabrication with random spatial variations of only ∆x = 1 nm can lead to resonance wavelength detunings of more than ∆λ = 1 nm 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been theoretically shown that isolated random modes could be selectively tuned and possibly coupled to each other by a local variation of the dielectric structure. [22][23][24] The recent realization of artificial coupled states in a disordered system by nano-oxidation represents, therefore, a remarkable achievement in controlling random modes. 25 However, the spatial steadiness of a single random mode size, shape, and position as a function of the spectral tuning is still an open question.…”
mentioning
confidence: 99%